Exploring and developing instrument measuring special education teachers’ knowledge in digital game-based learning pedagogy - Fei, Irene Yong Siew; Khairuddin, Khairul Farhah Binti; Nasri, Nurfaradilla Binti Mohamad (Journal of Education and e-Learning Research, 2025)
The teachers’ role has shifted from being solely knowledge transmitters and authority figures to facilitators who guide and support students through structured and pedagogically sound learning approaches. Digital game-based learning (DGBL) is an effective teaching pedagogy for students with learning disabilities, as it simplifies complex information by breaking it down into manageable steps and incorporating game design elements into instruction. This study aims to establish a foundational knowledge base for integrating game-based teaching within the context of special education teachers. It employed a cross-sectional design, utilizing a questionnaire for data collection. The data were analyzed through a pre-test, pilot test, and Exploratory Factor Analysis (EFA). Results show that the Kaiser-Meyer-Olkin (KMO) value ranges from 0.814 to 0.950, and Bartlett’s Test of Sphericity is significant (<0.001). For each construct, the total variance explained indicates good eigenvalues (>60%). Two items with factor loading below 0.6 were omitted. Finally, 52 items left were tested with Cronbach's Alpha and show high reliability (>0.8). The findings suggest that the Technological Pedagogical Content Knowledge – Games (TPACK-G) instrument has strong content validity, face validity, criterion validity, and internal reliability. This study provides a data-driven foundation that bridges teachers’ knowledge with the integration of digital game practices in special education classrooms. The EFA process contributed to the validation of the TPACK-G instrument, enabling accurate measurement of teachers’ knowledge in digital game-based learning pedagogy. Empirical data from this study indicate that special education teachers are prepared to implement instructional strategies involving digital game-based learning within inclusive digital learning environments.